2021
DOI: 10.1039/d0tc05845a
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong-lived room temperature phosphorescence from N and P codoped self-protective carbonized polymer dots for confidential information encryption and decryption

Abstract: Room-temperature phosphorescent (RTP) carbon dots offer unique opportunities in information security applications, but the delay time of such materials reported thus far is typically shorter than 10 s and thus...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 47 publications
0
49
0
Order By: Relevance
“…The encryption patterns of “O” and “V” are formed by spraying G‐CPDs, while the reference patterns of “L” and “E” are generated by using our previously prepared RTP emitting CPDs (Figure S31, Supporting Information). [ 38 ] The encrypted patterns of “O” and “V” are indistinguishable until the sample is further thermally annealed. The above demonstrations suggest that multicolor RTP emitting CPDs developed herein offers advanced platforms for anti‐counterfeiting applications.…”
Section: Resultsmentioning
confidence: 99%
“…The encryption patterns of “O” and “V” are formed by spraying G‐CPDs, while the reference patterns of “L” and “E” are generated by using our previously prepared RTP emitting CPDs (Figure S31, Supporting Information). [ 38 ] The encrypted patterns of “O” and “V” are indistinguishable until the sample is further thermally annealed. The above demonstrations suggest that multicolor RTP emitting CPDs developed herein offers advanced platforms for anti‐counterfeiting applications.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that a lattice spacing of 0.21 nm is in agreement with the in-plane lattice spacing of graphene (100 facets) and the spacing between graphite layers (100 facets). 18 What is more, as shown in Figure 2c, it is the corresponding particle size distribution histogram of Figure 2a, which revealed that the diameter of the as-prepared CPDs is in the range from 2.3 to 8.2 nm with an average size of 3.5 nm. The AFM image in Figure 2b,d shows the topographic height of the CPDs, which is similar to that of the TEM image.…”
Section: Resultsmentioning
confidence: 71%
“…From the top inset of Figure a, we can see that the CPDs have a polymer structure with a lower carbonization degree, while the CPDs at the bottom of the inset of Figure a have a polymer/carbon hybrid structure. These results demonstrate that a lattice spacing of 0.21 nm is in agreement with the in-plane lattice spacing of graphene (100 facets) and the spacing between graphite layers (100 facets) . What is more, as shown in Figure c, it is the corresponding particle size distribution histogram of Figure a, which revealed that the diameter of the as-prepared CPDs is in the range from 2.3 to 8.2 nm with an average size of 3.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…These characters show fluorescence under 365 nm UV light irradiation and display green phosphorescence after the 365 nm UV light is turned off. The Cl-CNDs may find applications in different fields such as fluorescent sensors, phosphorescent glow-in-the-dark materials, and security encryption ( Long et al, 2018 ; Wang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%